Pulse shaping methods for inter carrier interference reduction in OFDM system - N. M. A. E. D. Wirastuti; Ni Putu Lintang Anggitiadewi; Nyoman Pramaita (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
The weakness of the orthogonal freuency division multiplexing (OFDM) system is susceptible to the existence of carrier frequency offset (CFO) which causes the emergence of inter carrier interference (ICI) which causes a degradation of performance OFDM systems. This study aims to apply the suggested rectangular (REC) pulse and improved sinc-power (ISP) pulse shaping methods on OFDM system and determines ICI reduction with the effects of CFO over flat fading Rayleigh channels. The performance of each pulse shaping method is evaluated and compared based on parameter ICI power vs. normalized frequency offset, signal to interference ratio (SIR) vs. normalized frequency offset and bit error rate (BER) vs. energy bit per noise (Eb/No). The simulation result in terms of BER vs. Eb/No indicated that REC and ISP pulse shaping has better performance dealing with ICI reduction compared to OFDM system no applied pulse shaping. In addition, the ISP is able to mitigate ICI better than REC.